2017
DOI: 10.1021/acs.langmuir.7b00590
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic Silica Nanocapsules for Tunable Sustained Release and Cargo Protection

Abstract: Silica nanocapsules have attracted tremendous interest for encapsulation, protection, and controlled release of various cargoes due to their unique hierarchical core-shell structure. However, it remains challenging to synthesize silica nanocapsules having high cargo-loading capacity and cargo-protection capability without compromising process simplicity and biocompatibility properties. Here, we synthesized oil-core silica-shell nanocapsules under environmentally friendly conditions by a novel emulsion and biom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

6
1

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 53 publications
0
30
0
Order By: Relevance
“…4). The release of fipronil from the silica nanocapsules can fit well to the Higuchi model [4]. Fipronil release from SNC was considerably slow with 10 ± 2% on day 3 and followed by a gradual release to 25 ± 3% on day 19.…”
Section: Resultsmentioning
confidence: 56%
See 1 more Smart Citation
“…4). The release of fipronil from the silica nanocapsules can fit well to the Higuchi model [4]. Fipronil release from SNC was considerably slow with 10 ± 2% on day 3 and followed by a gradual release to 25 ± 3% on day 19.…”
Section: Resultsmentioning
confidence: 56%
“…Among many applications of nanotechnology in agriculture, development of nanoscale carriers for efficient and sustainable utilities of pesticides has received a lot of attention [1, 2, 3]. Specifically, encapsulation of pesticidal active ingredients within nanocarriers enhances their deliverability to target pests and enables control over their release kinetics, while at the same time protects them from premature degradation caused by direct exposure to ultraviolet light, low pH or heat [4, 5, 6]. These integrated controlled-release and protective properties of nanocarriers are expected to facilitate better efficacy of the encapsulated pesticide by prolonging its release on a target site, as compared to non-encapsulated formulations.…”
Section: Introductionmentioning
confidence: 99%
“…Thes ignificantly higher cytotoxicity of HDL NPs demonstrated their unique advantages over LDL NPs.T he drug release study of the curcumin nanocomposites showed an accelerated release of the drug at pH 4.5, but minimum release at pH 7.4 owing to the faster degradation of the silica shell in acidic solutions (Supporting Information, Figures S13 and S14). [11] Next, we performed the cytotoxicityt est on the 3D SKOV3t umor spheroids using HDL and LDL silica nanocomposites containing 100 ng mL À1 paclitaxel. [12] As we expected, after the treatment, the HDL group showed smaller spheroid volume and lower viability among all the treated groups ( Figure 4C,D;S upporting Information, Figure S15), demonstrating its enhanced tumor inhibition effect.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…We developed a novel and green biomimetic technology to form core-shell materials using dual-functional peptides [23][24][25][26][27][28][29]. These biomolecules have a unique two-module design, one module for surface activity to make stable droplets, and the other one for biosilisification activity.…”
Section: Introductionmentioning
confidence: 99%
“…After mixing, silica nanocapsules are generated with a well-controlled core-shell structure. The core size, which depends on the droplet size, can be tuned by using different homogenization energy input, different concentrations of peptide or different volume ratio of the oil phase, while the shell thickness can be controlled by adjusting the reaction time and the precursor concentration [25]. This bioinspired method is simple, sustainable, biocompatible, and doesn't involve any extreme conditions or toxic chemicals.…”
Section: Introductionmentioning
confidence: 99%